Ln–Pt electron polarization effects on the magnetic relaxation of heterometallic Ho– and Er–Pt complexes. Issue 21 (28th September 2018) - Yoshida, Takefumi; Izuogu, David C.; Zhang, Hai-Tao; Cosquer, Goulven; Abe, Hitoshi; Wernsdorfer, Wolfgang; Breedlove, Brian K.; Yamashita, Masahiro
Abstract : Heterometallic Ln–Pt complexes, with the formula [Ln2 Pt3 (H2 O)2 (SAc)12 ] (Ln = Ho(1 ), Er(2 ); SAc = thioacetate), were synthesized. Abstract : Heterometallic Ln–Pt complexes, with the formula [Ln2 Pt3 (H2 O)2 (SAc)12 ] (Ln = Ho(1 ), Er(2 ); SAc = thioacetate), were synthesized. From natural bond orbital (NBO) and local orbital locator (LOL) analyses and X-ray absorption fine structure (XAFS) measurements, it was clear that the Ln–Pt interactions or electron polarization occurred. Butterfly-type hysteresis was observed for both 1 and 2 . 1 and 2 underwent field-induced slow magnetic relaxation up to 4 K. These magnetic properties were induced by Ln–Pt electron polarization.